A systematic review of the effectiveness of children's behavioral health interventions in psychiatric residential treatment facilities. (June 2020) - Lanier, Paul; Jensen, Todd; Bryant, Katherine; Chung, Gerard; Rose, Roderick; Smith, Quinton; Lackmann, Lisa
Highlights: Children with emotional and behavioral disorders can receive treatment in PRTFs. A review identified many behavioral interventions and practices delivered in PRTFs. Evidence is insufficient to assess which interventions are effective. Abstract: Objective: The purpose of this systematic review was to synthesize quantitative or mixed-method studies that evaluate the efficacy of interventions with youth in the context of psychiatric residential treatment facilities (PRTFs) in the United States. Methods: Systematic review procedures were conducted to identify relevant studies, both published and from the gray literature in the United States. Search terms were informed via consultation with a university social science reference librarian, and four electronic databases were searched. Using a priori inclusion and exclusion criteria, team-based search procedures yielded a final sample of 47 relevant studies. Results: Studies varied with respect to publication status; sample size; research design; youth gender identity; youth racial/ethnic identity; youth behavioral, psychological, and developmental or intellectual concerns at intake; outcomes measures; and interventions evaluated. Evaluated interventions could be clustered into one of five categories: (a) modifications to system of treatment, (b) therapeutic modalities, (c) educational/alternative programs, (d) practice behaviors, and (e) post-discharge engagement. The majority of studies noted youth outcome improvements; however, some studies also yielded mixed, inconclusive, or null results. Conclusions: We would characterize the breadth and depth of research in this area to be insufficient in providing PRTF stakeholders a clear and firm understanding of "what works" for youth. Thus, one major implication of our review is the need for more research and efforts to incentivize the evaluation of ongoing practices in youth PRTFs. Still, this systematic review can serve as a convenient reference that can inform tentatively PRTF stakeholders' decisions about the selection of interventions or practice behaviors.